Low Frequency Radio Astronomy and the LOFAR Observatory Lectures from the Third LOFAR Data Processing School (Astrophysics and Space Science Library,, 2018)
This book presents lecture materials from the Third LOFAR Data School, transformed into a coherent and complete reference book describing the LOFAR design, along with descriptions of primary science cases, data processing techniques, and recipes for data handling. Together with hands-on exercises the chapters, based on the lecture notes, teach fundamentals and practical knowledge. LOFAR is a new and innovative radio telescope operating at low radio frequencies (10-250 MHz) and is the first of a new generation of radio interferometers that are leading the way to the ambitious Square Kilometre Array (SKA) to be built in the next decade. This unique reference guide serves as a primary information source for research groups around the world that seek to make the most of LOFAR data, as well as those who will push these topics forward to the next level with the design, construction, and realization of the SKA. This book will also be useful as supplementary reading material for any astrophysics overview or astrophysical techniques course, particularly those geared towards radio astronomy (and radio astronomy techniques).